2014
DOI: 10.1371/journal.pone.0095402
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Low Vitamin D and High Fibroblast Growth Factor-23 Plasma Levels Predicts an Adverse Outcome in Patients with Coronary Artery Disease

Abstract: ObjectiveVitamin D and fibroblast growth factor-23 (FGF-23) are related with cardiovascular disorders. We have investigated the relationship of calcidiol (vitamin D metabolite) and FGF-23 plasma levels with the incidence of adverse outcomes in patients with coronary artery disease.MethodsProspective follow-up study of 704 outpatients, attending the departments of Cardiology of four hospitals in Spain, 6–12 months after an acute coronary event. Baseline calcidiol, FGF-23, parathormone, and phosphate plasma leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 36 publications
(37 reference statements)
3
54
0
Order By: Relevance
“…It was recently demonstrated that Klotho, which determines the tissue-specific signaling of FGF-23, is expressed in human arteries and human aortic smooth muscle cells (Donate-Correa et al, 2013), suggesting that FGF-23 could affect vascular tissues in an endocrine fashion (Lim et al, 2012). FGF-23 may also modulate progression and development of coronary atherosclerosis through inhibition of vitamin D activation (Tuñón et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that Klotho, which determines the tissue-specific signaling of FGF-23, is expressed in human arteries and human aortic smooth muscle cells (Donate-Correa et al, 2013), suggesting that FGF-23 could affect vascular tissues in an endocrine fashion (Lim et al, 2012). FGF-23 may also modulate progression and development of coronary atherosclerosis through inhibition of vitamin D activation (Tuñón et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factor 23 may also modulate progression and development of coronary atherosclerosis through its inhibition of vitamin D activation. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the relationship between FGF-23 levels and CV mortality was also reported for patients with no CKD3 and for community-living individuals 4. FGF-23 was shown to be a strong predictor of CV mortality in patients with coronary artery disease (CAD),5 as well as in patients with acute or chronic heart failure (HF) 6 7…”
Section: Introductionmentioning
confidence: 90%